The Effect of Big Data Adoption on Regional Bank Profitability: Simulated Data in the Financial Planning - Karona Cahya Susena; Nenden Restu Hidayah; Sukrisno Sukrisno; Made Setini (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Digital transformation, marked by the era of financial planning 5.0, presents both a challenge and an opportunity for regional banks. While large institutions rapidly adopt data-driven strategies, regional banks often lag due to resource constraints, potentially harming their profitability and competitiveness. This study examines the role of big data adoption within this modern framework to optimize the financial performance of regional banks. Using a quantitative approach with a multiple regression model, this research simulates data from ten regional banks to test the effects of big data adoption, operational efficiency, and risk management on two key profitability indicators: Return on assets and net interest margin. The analysis results show that big data adoption has a significant positive correlation with both profitability measures. In contrast, higher operational costs and increased non-performing loans negatively affect bank profitability. These findings demonstrate that strategic investment in data technology, when integrated with efforts to improve operational governance and human resource capabilities, can be a crucial lever for enhancing the financial performance and sustainability of regional banks in the digital age.